Clowning in education: laughter and joy in teaching practice - Michelini da Silva, Felipe Augusto (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2026)
In this article, I share my reflections on laughter and joy at school as a clown teacher. By approaching clown artistry as a possibility for training teachers, we will think about the concept of a teaching figure who, by exercising the practices and philosophies of clowning, can allow themselves to laugh at themselves and with the students, in search of a collective engagement so that laughter and joy permeate educational processes. Finally, we argue that clowning practices are a way of exercising laughter as a form of subversion and joy as strength in struggle, thus shaking up traditional and colonial educational structures.